Resistance Training and Testosterone Levels in Male Patients with Chronic Kidney Disease Undergoing Dialysis. (3rd April 2014) - Molsted, Stig; Andersen, Jesper L.; Eidemak, Inge; Harrison, Adrian P.; Jørgensen, Niels
Abstract : Background. We investigated serum testosterone and insulin-like growth factor 1 (IGF-1) levels' associations with muscle fibre size and resistance training in male dialysis patients. Methods. Male patients were included in a 16-week control period followed by 16 weeks of resistance training thrice weekly. Blood samples were obtained to analyse testosterone, luteinizing hormone (LH), IGF-1, and IGF-binding protein 3. Muscle fibres' size was analysed in biopsies from m. vastus lateralis . Results. The patients' testosterone levels were within the normal range at baseline (n = 20 ) (19.5 (8.2–52.1) nmol/L versus 17.6 (16.1–18.0), resp.) whereas LH levels were higher (13.0 (5.5–82.8) U/L versus 4.3 (3.3–4.6), P < 0.001, resp.). IGF-1 and IGF-binding protein 3 levels were higher in the patients compared with reference values (203 (59–590) ng/mL versus 151 (128–276), P = 0.014, and 5045 (3370–9370) ng/mL versus 3244 (3020–3983), P < 0.001, resp.). All hormone levels and muscle fibre size (n = 12 ) remained stable throughout the study. Age-adjusted IGF-1 was associated with type 1 and 2 fibre sizes (P < 0.05 ). Conclusion. Patients' total testosterone values were normal due to markedly increased LH values, which suggest a compensated primary insufficiency of the testosterone producing Leydig cell. Even though testosterone values were normal, resistance training was not associated with muscle hypertrophy. This trial is registered with ISRCTN72099857 .